Using a Streamlined Procedure to Combine AlCl3 and Chloroacetamide to Create a New Ionic Liquid - B. Hasan, Bassam; A. Salman, Taghried (Al-Nahrain Journal of Science, 2023)
By reacting AlCl3 with chloroacetamide (CA) at the optimal mole ratio (2:1), a new type of ionic liquid was created in addition to the group of ionic liquids (aluminum chloride-amide). With an ionic conductivity of 0.34 mS/cm, the resultant clear brown ionic liquid demonstrated good thermal stability at ambient temperature in a glove box filled with nitrogen gas. Its coordination was established using FT-IR. Measurements have been made of additional physical characteristics including viscosity and cyclic voltammetry.